Model for fatigue crack growth analysis - Borges, M. F. M. (2020)
precisely. A literature review about analytical models showed a great number of models developed for specific materials and loading conditions. A numerical analysis of a CT specimen made of 304L stainless steel showed the complex influence of material parameters on FCG, which also depends on loading parameters, geometry and environmental conditions. Therefore an alternative to analytical models is proposed here, based on plastic CTOD, assuming that this is the crack driving force. A material law must be first obtained relating da/dN with plastic CTOD range, p, obtained numerically using the finite element method or experimentally using DIC. This law changes with material and includes all material parameters and also environmental conditions (temperature and atmosphere) . The design of a specific cracked component is made using numerical tools in order to obtain p for different crack lengths. This second analysis includes the effect of geometrical and loading parameters.